Chiral Thermally Activated Delayed Fluorescence Materials Based on R/S‐N2, N2′‐Diphenyl‐[1, 1′‐binaphthalene]‐2, 2′‐diamine Donor with Narrow Emission Spectra for Highly Efficient Circularly Polarized Electroluminescence. (1st July 2021) - Yan, Zhi‐Ping; Liu, Ting‐Ting; Wu, Ruixia; Liang, Xiao; Li, Zhi‐Qiang; Zhou, Liang; Zheng, You‐Xuan; Zuo, Jing‐Lin
Abstract: In this study, two pairs of chiral thermally activated delayed fluorescence (TADF) materials enabling circularly polarized luminescence (CPL) named R / S ‐ p ‐BAMCN (rod‐shape) and R / S ‐ o ‐BAMCN (helix‐shape) are prepared based on a new pair of chiral donor (D*), R / S ‐ N 2, N 2 ′‐diphenyl‐[1, 1′‐binaphthalene]‐2, 2′‐diamine ( R / S ‐BAM ), and two cyano (CN) acceptors. Due to the rigid molecular structure and special intramolecular arrangement, the chiral TADF materials show high photoluminescence quantum efficiency (up to 0.86) with narrow full‐width at half‐maximum (38 nm in cyclohexane, 51 nm in toluene) and photoluminescence dissymmetry factor (| g PL |) up to 5.3 × 10 −3 . Particularly, the circularly polarized OLEDs (CP‐OLEDs) with rod‐shaped R / S ‐ p ‐BAMCN as the emitter show high device performances with the maximum external quantum efficiency nearing 28%. Meanwhile, the semi‐transparent CP‐OLEDs based on helix‐shaped R / S ‐ o ‐BAMCN exhibit obvious circularly polarized electroluminescence (CPEL) properties with the electroluminescence | g EL | factors around 4.6 × 10 −3 . The strategy of rigid D*‐A‐D* structure with special arrangement of chiral donor provides a direct way to obtain efficient CP‐TADF materials with narrow emission spectra and promising CPL properties for better CPEL performance. Abstract : By constructing a chiral donor and acceptor strategy, a universal approach to efficiently construct CP‐TADF molecules is proposed with obvious CPL properties and a narrow FWHM of 38 nm. Furthermore, highly efficient CP‐OLEDs with an EQE nearing 28% and | g EL | of 4.6 × 10 −3 are achieved based on the constructed rod‐ and helix‐shaped CP‐TADF molecules, respectively.